The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s00432-008-0391-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of Survivin and CD44v6 in laryngeal cancer surgical margins

Abstract: Immunohistochemical assessment of both Survivin and CD44v6 status in negative surgical margin may be a valuable approach for predicting recurrence and survival after curative surgery for laryngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 15 publications
(16 reference statements)
5
19
1
Order By: Relevance
“…Recently, Zhao et al reported that immunohistochemical assessment of CD44v6 in a negative surgical margin would be a valuable approach for predicting recurrence and survival after curative surgery for laryngeal cancer (36). Some authors showed that CD44v6 could be associated with cancer progression, metastasis, and recurrence (36,46). Our data indicate that CD44v6 expression is associated with regional lymph node metastasis, POI, NAC, DOI, perineural invasion, and local recurrence in OTSCC.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Recently, Zhao et al reported that immunohistochemical assessment of CD44v6 in a negative surgical margin would be a valuable approach for predicting recurrence and survival after curative surgery for laryngeal cancer (36). Some authors showed that CD44v6 could be associated with cancer progression, metastasis, and recurrence (36,46). Our data indicate that CD44v6 expression is associated with regional lymph node metastasis, POI, NAC, DOI, perineural invasion, and local recurrence in OTSCC.…”
Section: Discussionsupporting
confidence: 52%
“…It was also hypothesized in the mechanism of tumor local recurrence that this elevated risk may be due to undetected tumor cells present in surgical margins thought to be negative by conventional light microscopy (9-11). Recently, to improve the detection of residual cancer cells or tumor-related precursor lesions remaining in histologically negative margins, molecular margin analysis was proposed and has now been used to observe and predict local recurrence of head and neck cancers (9,12,36). We therefore focused on the expression of molecules relevant to CSCs in tumor satellites at the tumor/ host interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kawano et al found CD44s and CD44v6 staining correlated with prognosis in a series of 57 patients treated with surgery and radiotherapy (35). Zhao et al analyzed margins after surgery for 112 HNSCC patients and found that CD44v6 presence in these margins, detected with immunohistochemistry, was predictive of recurrence (36). Wang et al (37) found that one CD44 isoform (v10) was associated with reduced disease free survival in HNSCC.…”
Section: Discussionmentioning
confidence: 99%